Electrical properties of n-SnS₂/n-CdIn₂Te₄ heterostructure - Gorley, P.M.; Grushka, Z.M.; Grushka, O.G.; Gorley, P.P.; Zabolotsky, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Using the method of deposition over the optical contact, the authors created nSnS2/n-CdIn₂Te₄
heterojunction and investigated temperature evolution of its currentvoltage
characteristics under the forward bias U ≤ 3 V. Analyzing temperature
dependence of the curves obtained, the main mechanisms of current transport through the
semiconductor contact were determined, allowing prediction of successful possible
applications of the heterojunction studied under high temperatures and elevated radiation
due to the parameters of the base semiconductors and the diode structure itself.